THE ROLE AND SIGNIFICANCE OF THE PORTRAIT GENRE IN AESTHETIC EDUCATION OF V-VIII CLASS STUDENTS OF GENERAL SECONDARY SCHOOLS - Khasanov. Kh. Kh (American Journals, 2024)
In this article, the aesthetic education of schoolchildren by means of visual arts is justified from a scientific and theoretical point of view, the role of the portrait genre in providing the creative activity opportunities of all schoolchildren is revealed.
Keywords: school, student, education, visual arts, aesthetics, culture.